The dynamics of vulnerability: why adapting to climate variability will not always prepare us for climate change. (23rd April 2015) - Dilling, Lisa; Daly, Meaghan E.; Travis, William R.; Wilhelmi, Olga V.; Klein, Roberta A.
<x xml:space="preserve">Abstract</x> Recent reports and scholarship suggest that adapting to current climate variability may represent a 'no regrets' strategy for adapting to climate change. Addressing 'adaptation deficits' and other approaches that target existing vulnerabilities are helpful for responding to current climate variability, but we argue that they may not be sufficient for adapting to climate change. Through a review and unique synthesis of the natural hazards and climate adaptation literatures, we identify why the dynamics of vulnerability matter for adaptation efforts. We draw on vulnerability theory and the natural hazards and climate adaptation literatures to outline how adaptation to climate variability, combined with the shifting societal landscape can sometimes lead to unintended consequences and increased vulnerability. Moreover, we argue that public perceptions of risk associated with current climate variability do not necessarily position communities to adapt to the impacts from climate change. We suggest that decision makers faced with adapting to climate change must consider the dynamics of vulnerability in a connected system—how choices made in one part of the system might impact other valued outcomes or even create new vulnerabilities. We conclude by suggesting the need for greater engagement with various publics on the tradeoffs involved in adaptation action and for improving communication about the complicated nature of the dynamics of vulnerability. WIREs Clim Change 2015, 6:413–425. doi: 10.1002/wcc.341 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.